SÍNTESE HIDROTÉRMICA E ATIVIDADE MICROBIOLÓGICA DE TITANATOS RECOBERTOS COM COBRE - SAMPAIO, Julia Bortolusso; PESSOA, Kauane Kashyiama; SILVA, Thais; KURAMOTO, Mariana Yumi Simões; DIAS, Fabricia E. M.; RODRIGUES, Daniela Cristina Manfroi (ANAIS DO ENIC, 2020)
-